1999
DOI: 10.1159/000053594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eotaxin on the Generationof Reactive Oxygen Species from Eosinophil Cell Line, YY-1

Abstract: Background: The CC chemokine eotaxin is a selective chemoattractant for eosinophils. Eosinophils have been considered to be the major effector cells in allergic inflammation, since not only eosinophil-specific granule proteins but also reactive oxygen species (ROS) from eosinophils may cause the damage to the cells or tissue of the mucosal epithelium. In this study, we examined the effect of eotaxin on ROS from an eosinophil cell line, YY-1. Methods: ROS in luminol-dependent reaction were examined. Calcium ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Consistent with this, CCL11 promoted migration and ROS production in microglia, as reported previously in eosinophils (Honda et al, 1999). In addition, we showed that microglia predominantly express CCR3, the main receptor for CCL11.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with this, CCL11 promoted migration and ROS production in microglia, as reported previously in eosinophils (Honda et al, 1999). In addition, we showed that microglia predominantly express CCR3, the main receptor for CCL11.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our data suggest that microglia are the main effectors of CCL11 in the CNS. Consistent with this, CCL11 promoted migration and ROS production in microglia, as reported previously in eosinophils (Honda et al, 1999). Moreover, CCL11-mediated microglial ROS potentiated excitotoxic neuronal death, a causative mechanism of neurodegeneration in various neurological disorders.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, it is difficult to obtain sufficient eosinophils for functional analysis due to their small numbers in the peripheral blood cells. We therefore checked expression of IL-18R in the human eosinophilic cell lines, YY-1 [21,22] and EoL-1 [23] and other human cell lines including B cells (NALM6, RAMOS, DND39), myeloma cells (U266), T cells (Jurkat), monocytic cells (U937) and basophilic cells (KU812). As shown in Fig…”
Section: Expression Of Il-18 > Chain Receptor Mrna In Human Peripheramentioning
confidence: 99%
“…Since YY-1 cells are known to differentiate into more mature eosinophils following treatment with n-butyric acid (n-BA), as measured by the cellular contents of granules and cytokines [21,22], the effect of n-BA on the expression of § chain of IL-18R in YY-1 cells was studied by RT-PCR and FACS analyses. As shown in Fig.…”
Section: Treatment Of Yy-1 Cells With N-butyric Acid Enhances Expressmentioning
confidence: 99%
See 1 more Smart Citation